The therapeutic potential of nabilone based on the results of clinical trials. - Jan Maciej Kapała; Julia Alicja Lewandowska; Łukasz Puchała (Polish Pharmaceutical Society, 2020)
Nabilone is a synthetic cannabinoid which i.a. via agonism of cannabinoid receptors (CB1 and CB2) presents an extremely diverse therapeutic range in current clinical trials. The purpose of this review is to evaluate the outcomes of selected articles with emphasis on the safety, pharmacotherapy efficacy and potential of nabilone. A literature review was performed in August 2020. Three databases (PubMed, ClinicalTrials and Cochrane Library) were searched. Chosen for review articles were published in 2010 - 2020. The selection of publications was made independently by two authors. Searched studies include randomized controlled trials (RCTs), open-label clinical trials and retrospective cohort studies. For review there were identified 23 articles: 20 RCTs and 2 open-label clinical trials and 1 retrospective cohort study. Out of the selected 4 were related to the improvement of the quality of life in patients with advanced cancer and the treatment of nausea and vomiting (n = 539), 4 focused on the addiction therapy (n = 65), 5 were related to the treatment of neuropathic pain, chronic pain and hyperalgesia (n = 202), 2 analysed the effect on agitation in Alzheimer's disease (n = 76), 2 examined effects on cognitive functions and cardiovascular symptoms (n = 38), 1 concerned the use of nabilon for treatment of non-motor symptoms in Parkinson's disease (n = 38), 3 focused on the effects on sleep condition (n = 50), 1 was related to the treatment of spasticity (n = 11), and 1 concerned the use of nabilon for the treatment of obsessive-compulsive disorder (n = 12). Nabilone has potential in the treatment of sleep disorders, spasticity, pain, agitation in patients with Alzheimer's disease and non-motor symptoms in Parkinson's disease. However, it is not efficient in the treatment of cancer comorbidities and in reducing nausea and vomiting. Nabilone does not reduce cravings and amount of marijuana intake in cannabis dependent patients, but it suppresses full spectrum of accompanying symptoms and does not interfere with the work of the cardiovascular system. Presented side effects were mild and short-lived in majority cases and included i.a. drowsiness, nausea, dry mouth, fatigue and dizziness.